IDENTIFIKASI FAKTA DAN OPINI DALAM TEKS EKSPOSISI “MERETAS ASA, MEMBANGUN WIBAWA” DENGAN MEDIA KARTU - Rahma Meutia Latifah; Siti Iyar; Eli Syarifah Aeni (IKIP Siliwangi, 2019)
The real problem found in the field is the number of students who think that facts and opinions are the same things, even when describing the meaning and example there are still things that are not appropriate. Facts are events or real events that really happened. The opinion is a statement that contains ideas or assumptions of both individuals and groups. This study aims to determine the skills of students to identify facts and opinions and the extent to which students can sort out the facts and opinions contained in the exposition text with card media. Researchers in conducting this study used a qualitative approach method with descriptive analysis. The results obtained indicate that the knowledge and ability of students in identifying facts and opinions is good enough can be reviewed from the answers obtained, namely, there are 59% of students answered correctly and 41% of students answered incorrectly. There were 12 students who received the KKM score and 8 students who received fewer scores from the KKM. The result is 60% and 40%, indicating that students already understand and are able to show which facts and opinions. Therefore, the implementation of card media that is applied when identifying facts and opinions in exposition text with card media is quite successful in increasing students' knowledge, understanding and abilities.